(untitled) (The Pakistan Development Review, 1993)
This study is an attempt to extend the analysis of change in the land distribution over time, to 1991. In an earlier study we have shown a strong tendency towards increasing concentration of operated area, between 1972 and 1980. This concentration was seen to be engendered by a dynamic associated with the High Yielding Variety (HYV) technology. This study attempts to examine whether the HYV dynamic has continued to increase concentration of area over the decade of the 80s. The recently concluded Agricultural Census of 1991, allows us to do this. Our major result is that concentration of operated area has increased further between 1980 and 1991. However, the long run nature of concentration found here, points to another possible explanation. The HYV dynamic may have been one initiating change in a series of price and technology changes, leading to continual change in factor use in the direction of concentration.